Етнічна геополітика як напрям державної політики - Гольцов, Андрій Геннадійович (My University, 2009)
Наведено визначення такого напрямку геополітичних досліджень, як етнічна геополітика. Розглянуто прикладний вимір етнічної геополітики. Виділено стан державної етнічної геополітики. Аналізовано різновиди внутрішньодержавної етнічної геополітики: імперська (на прикладах Росії та Китаю), дискримінаційна, асиміляційна тощо. The definition of such a direction of geopolitical research as ethnic geopolitics is given. The applied dimension of ethnic geopolitics is considered. The state of state ethnic geopolitics is highlighted. Varieties of internal state ethnic geopolitics are analyzed: imperial (on the examples of Russia and China), discriminatory, assimilation, etc.
Keywords: етнічна геополітика; ethnic geopolitics; державна політика; state policy